Collection of Multi-crop Germplasm from Nagaland, India and their Range of Diversity - SINGH, S.K.; MISRA, A.K. (Indian Journal of Hill Farming, 2015)
Exploration and collection trips were undertaken comprising Dimapur, Kohima Mokokchung and Tuensang districts of Nagaland in order to collect crop germplasm diversity. A total of 306 multicrop germplasm accessions collected randomly from the unexplored pockets of the surveyed areas, and their crop group wise break up is as follows; cereals 141, pseudocereals 14, grain legumes 59, vegetables 22, oilseeds 45, spices 19 tuber crop 04 and fruits 02. Characterized germplasm included rice (88 accs.), maize (50 accs.), rice bean (14 accs.), rapeseed and mustard (29 accs.) and Perilla (10 accs.). This paper discusses the pattern of variability of collected germplasm and the observations on field evaluation. The promising genotypes were also identified. Local indigenous technical knowledge of conservation of seed by the farmers was also recorded during exploration.